Fluorescein angiography of anterior uveal melanocytic tumours. Issue 5 (May 1988) - Dart, J. K.; Marsh, R. J.; Garner, A.; Cooling, R. J.
Abstract : A retrospective analysis of 32 cases of anterior uveal melanocytic tumours included 14 cases in which the tumours could be categorised histologically as malignant, of intermediate cytology with equivocal features of malignancy, or as benign progressive naevi. An additional eight cases without a histological diagnosis were included as benign naevi, because there had been no change in their clinical characteristics after a minimum follow-up of four years. Clinical features and iris fluorescein angiographic (IFA) findings were analysed with respect to these groups in an attempt to identify features predictive of malignant or locally invasive behaviour. Very small tumours were more likely to be benign (p = 0.029). Glaucoma and episcleral vascular dilatation occurred in ciliary body tumours only. Tumours involving the anterior chamber angle proved more likely to be malignant (p = 0.019). IFA showed a disorganised vasculature and gross late leakage in 4/7 (56%) malignant melanomas as well as in 2/6 (33%) tumours with intermediate cytology. No benign tumours showed these features. Four out of nine (44%) benign tumours, but no tumours with malignant or intermediate cytology, showed complete masking of fluorescence. Early leakage of dye from tumour vessels and a geometric tumour vasculature were not specific features of any tumour category. IFA correlated with the cytology and behaviour of anterior uveal melanocytic tumours in 11/22 (50%) of our cases.